Oil Price Movements and Nigeria’s Economic Indicators - Mgbame, C.O; Donwa , P.A; Ogbaisi, S.A (Asian Journal of Empirical Research, 2015)
This study examines the impact of changes in oil price movements on GDP and Unemployment within the context of the Nigerian economy. The methodology approach adopted was library research, focused on content review of extant literature. From the review of literature, findings and recommendations were arrived at. This study concludes that oil price movements do not significantly affect the economy on the whole since unemployment level in the country is still very high. However, there is a direct relationship with GDP because as oil price rises GDP also rises. Since Nigeria is a mono cultural economy and the price of oil has been falling in recent time, it is recommended that Nigeria should embrace other sectors of the economy like agriculture and solid minerals.